Kontekstualisasi Wawasan Islam Kebangsaan Kiai Abdul Muchith Muzadi - Ahidul Asror (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2016)
This article seeks to reveal Kiai Muchith Muzadi’s thought on the Islamic nationalism in Indonesia. It deals with a number of issues such as state form, the meaning of politics within nation-state life, and the relation of Islam and Pancasila. The article also attempts to answer problematic discourse on contemporary Islam which, within recent decades, (re)rises the principles of nationalism into public discussion. Muchith argues that Negara Kesatuan Republik Indonesia (NKRI/The Unitary State of the Republic of Indonesia) has been an ultimate state form for the Indonesian people. Therefore, this is a duty for the Indonesian Muslims, as Indonesia’s majority inhabitant, to actively take a role and involve themselves in guarding Indonesia and its unity. Muchith also sees no relevant necessary to replace the state form with other systems such as khil?fah and Islamic state. To him, politics is a mere means to fight for interests carried out with Islamic principles coupled with nationalism values in order to establish national integration and achieve the shared ideals. Muchith maintains that Pancasila along with its values is compatible with Islam and this is why the Indonesian Muslims should accept it as the state ideology.